Determination of MIC and MBC of Peperomia pellucida Extract Against Aggregatibacter actinomy-cetemcomitans Using Serial Dilution and Colony Count Assay - Dewi Lidya Ichwana Nasution; Sri Tjahajawati; Ratna Indriyanti; Amaliya Amaliya; Muhammad Ammar Permadi (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Periodontitis is an infectious disease that damages periodontal tissues and may lead to tooth loss. Aggregatibacter actinomycetemcomitans is one of the main pathogenic bacteria associated with periodontitis. Peperomia pellucida (L.) Kunth contains flavonoids, alkaloids, and tannins with antibacterial potential. This study evaluated its effectiveness against A. actinomycetemcomitans and determined its Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Materials and Methods: This laboratory experimental study used a post-test-only control group design. Antibacterial testing was performed using the serial dilution method in eight groups: extract concentrations of 3.125%, 6.25%, 12.5%, 25%, 50%, and 100%, 0.2% chlorhexidine as the positive control, and distilled water as the negative control. MIC was assessed by bacterial growth on Mueller–Hinton Agar, while MBC was determined by colony counts (CFU/mL). Data were analyzed using Kruskal–Wallis and Mann–Whitney tests. Results: Peperomia pellucida extract showed antibacterial activity against A. actinomycetemcomitans. MIC was achieved at 6.25% concentration with 92.5% inhibition, while MBC was achieved at 12.5% concentration with 100% bactericidal effect. Conclusion: Peperomia pellucida extract effectively inhibited and killed A. actinomycetemcomitans, with greater antibacterial activity at higher concentrations.